The influence of embryo stage on obstetric complications and perinatal outcomes following programmed compared to natural frozen-thawed embryo transfer cycles: a systematic review and meta-analysis - Zhao, Zhonghua; Chen, Yan; Deng, Hongxia; Huang, Lu; Lu, Danhua; Shen, Xiaoyang; Xu, Liangzhi (Frontiers in Endocrinology, 2023)
Objective: To investigate the effect of embryo stage at the time of transfer on obstetric and perinatal outcomes in programmed frozen-thawed embryo transfer (FET) versus natural FET cycles.Setting：Not applicable. Patient(s): Women with programmed frozen-thawed embryo transfer (FET) and natural FET. Intervention(s): The PubMed, MEDLINE, and EMBASE databases and the Cochrane Central Register of Controlled Trials (CCRT) were searched from 1983 to October 2022.Twenty-three observational studies were included.Primary Outcome Measure: The primary outcomes were hypertensive disorders of pregnancy (HDPs), gestational hypertension and preeclampsia (PE). The secondary outcomes were gestational diabetes mellitus (GDM), placenta previa, postpartum haemorrhage (PPH), placental abruption, preterm premature rupture of membranes (PPROM), large for gestational age (LGA), small for gestational age (SGA), macrosomia, and preterm delivery (PTD).programmed FET cycles and natural FET cycles.The risks of HDPs, gestational hypertension, PE, GDM,LGA, macrosomia, SGA, PTD, placenta previa, PPROM, and PPH were increased in programmed FET cycles versus natural FET cycles with overall embryo transfer and blastocyst transfer, but the risks were not clear for cleavage-stage embryo transfer.